A clinical profile of liver function tests in COVID-19 patients at tertiary care centre from north India - Priyadarshi, B. P; Kumar, Avdhesh; Singh, Vipul; Varma, Sanjay Kumar; Yadav, Ravi; Pandey, Pankaj; Tripathi, Sanjeev (International Journal of Research in Medical Sciences, 2021)
Background: The coronavirus is a large group of virus, which spread rapidly as an epidemic in china and was named initially as 2019 novel corona virus and subsequently named as Coronavirus disease 2019 (COVID-19) by World Health Organization (WHO). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to a dramatic loss of human life globally and manifests a variety of clinical symptoms varying from fever, cough, headache, myalgias, nausea, vomiting to more severe pneumonia, ARDS, septic shock and multiorgan failure. SARS-CoV-2, primarily affect respiratory system but COVID-19 patients also have varying levels of liver injuries or liver dysfunction. This retrospective study was designed to analyze the clinical features, liver function and duration of hospital stay with confirmed cases of covid-19 in a tertiary care centre. Methods: We conducted a cross-sectional study in the Isolation ward, Level -2 Covid Hospital, Government Medical College, Kannauj, Uttar Pradesh (India), from April to June 2021. A detailed history and examination was carried out as per the pre-designed proforma. The liver function test included alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and total bilirubin. Patients were considered with abnormal LFTs when any value of these tests was higher than upper limit of normal. Results: One hundred and ten patients with covid-19 were enrolled during the study period. There were 74 males (67.2%) and 36 (32.7%) females. The mean age of study population was 49.07±12.05 years. In present study, the mean value of serum bilirubin, SGPT, SGOT and ALP were 0.85±0.47 mg/dl, 74.6±66.9 IU/L, 48.45±36.86 IU/L and 229.25±69.79 IU/L, respectively. In present study, the abnormal liver function was seen in 67.2 % cases with COVID-19 patients. The mean duration of hospital stay among normal LFT and abnormal LFT patients group were 13.33±2.12 and 17.10±2.07 days, respectively. Conclusions: The present study highlighted that abnormal liver function was observed in 67.2% cases with COVID-19 patients. Further research should focus on the cause of liver injury in covid 19 and on treatment and outcome.